Production and sex‐pheromonal activity of alkaloid‐derived androconial compounds in the danaine butterfly, Parantica sita (Lepidoptera: Nymphalidae: Danainae). (17th August 2016) - Honda, Keiichi; Honda, Yasuyuki; Matsumoto, Junya; Tsuruta, Yoshiaki; Yagi, Wataru; Ômura, Hisashi; Honda, Hiroshi
Abstract : Close associations of certain lepidopteran taxa with pyrrolizidine alkaloids (PAs), a typical class of plant secondary metabolites, have been well documented from the perspective of evolutionary ecology. Male danaine butterflies are thought to utilize PAs as precursors for the production of dihydropyrrolizines [e.g. danaidone (DO) and hydroxydanaidal (HD)] in their two distinct androconial organs, viz. alar scent organs (sex brands) and abdominal hairpencils. However, little is known about the quantitative profiles of these compounds in danaines, the mechanism for their formation in the androconial organs, or their biological functions, particularly in mating behaviour. The present study addressed these unanswered questions posed for males of the danaine butterfly, Parantica sita . Chemical analyses of androconial extracts revealed considerable seasonal/regional and individual variations of the amounts of DO (the major dihydropyrrolizine produced) and 7 R ‐HD (the 7 R ‐enantiomer of HD detected in this study) found in the two organs. These variations seemed to depend primarily on the age of the male and the phenological traits of PA‐containing plants available. Males were found to acquire an adequate capability to produce DO 1 week after eclosion. DO was shown to be produced exclusively in the sex brand and subsequently physically transferred to the hairpencil through a contact behaviour between the two organs, here termed 'perfuming behaviour'. The results of behavioural experiments with PA‐fed and PA‐unfed males that were allowed to compete for mates, combined with the positive electroantennographic (EAG) responses of the female, to both DO and 7 R ‐HD, led to the conclusion that either or both of these compounds can act as the sex pheromone. Oral administration of PAs to males indicated that DO can be biosynthesized from various PA precursors, while 7 R ‐HD, unlike in arctiid moths, is derived only from PAs with the 7 R ‐configuration. The putative biosynthetic pathways of DO and 7 R ‐HD, and the evolutionary provenance of the binate androconial system in the Danainae are also discussed.